2016
DOI: 10.1038/srep33864
|View full text |Cite
|
Sign up to set email alerts
|

Wild chimpanzees modify modality of gestures according to the strength of social bonds and personal network size

Abstract: Primates form strong and enduring social bonds with others and these bonds have important fitness consequences. However, how different types of communication are associated with different types of social bonds is poorly understood. Wild chimpanzees have a large repertoire of gestures, from visual gestures to tactile and auditory gestures. We used social network analysis to examine the association between proximity bonds (time spent in close proximity) and rates of gestural communication in pairs of chimpanzees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 131 publications
(178 reference statements)
2
65
0
Order By: Relevance
“…We therefore examined the predictors of reciprocated close proximity between pairs of chimpanzees i.e., what predicts the presence of a reciprocated close proximity bond between Chimpanzee A and Chimpanzee B? In previous research, we have shown that the presence of a reciprocated close proximity bond is predicted by a longer duration of mutual grooming and received grooming between pairs of chimpanzees (Roberts and Roberts, 2016). Here we extended these findings and showed that a specific set of signals—greetings, gestures to initiate mutual grooming, gestures to initiate receiving grooming, gestures to initiate travel, and synchronized low intensity pant-hoot—predicted the presence of a reciprocated close proximity bond between pairs of chimpanzees.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We therefore examined the predictors of reciprocated close proximity between pairs of chimpanzees i.e., what predicts the presence of a reciprocated close proximity bond between Chimpanzee A and Chimpanzee B? In previous research, we have shown that the presence of a reciprocated close proximity bond is predicted by a longer duration of mutual grooming and received grooming between pairs of chimpanzees (Roberts and Roberts, 2016). Here we extended these findings and showed that a specific set of signals—greetings, gestures to initiate mutual grooming, gestures to initiate receiving grooming, gestures to initiate travel, and synchronized low intensity pant-hoot—predicted the presence of a reciprocated close proximity bond between pairs of chimpanzees.…”
Section: Discussionmentioning
confidence: 86%
“…Here we show that joint coalitionary aggression in the form of synchronized high intensity pant-hoots may be one way in which these relationships are maintained. On the behavioral level, aggressive signals, particularly those that are deep, sharp, sudden, and high volume gestures, are associated with high arousal and induce arousing, fear reactions in the recipients (Bryant, 2013; Roberts and Roberts, 2015, 2016). On the physiological level, aggressive signaling can affect the recipient's nervous system by inducing an increase in plasma cortisol release (Beerda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We aimed to expand Plooij's (, ) early descriptive work by conducting the first systematic, quantitative study on behavioural markers of intentional communication and taking into account potential within‐species variability. Recent work on chimpanzees living in different study populations has shown that social factors such as context, familiarity and social bond (Fröhlich et al., ; Fröhlich, Wittig, & Pika, ; Luef & Pika, ; Roberts & Roberts, ; Schel et al., ), and also individual or demographic factors (mother's experience in rearing offspring, sex and study site) can have a profound influence on signal production (Fröhlich et al., ; Fröhlich, Wittig et al., , ). We therefore need more systematic data on the communicative behaviour of great apes in the wild to better understand how communicative development relates to social opportunities in the environment.…”
Section: Introductionmentioning
confidence: 99%